2015
DOI: 10.1111/jam.12884
|View full text |Cite
|
Sign up to set email alerts
|

Rapid differentiation of mycobacteria by simplex real-time PCR with melting temperature calling analysis

Abstract: Rapid differentiation of mycobacteria could shorten the diagnostic time of mycobacterial diseases. It is also helpful for achieving optimal therapy and appropriate patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Although semi-automated culture systems have reduced the time required for the tests, traditional tests for identification between MTB and NTM species still suffer from disadvantages (Kazumi and Mitarai, 2012;Şamlı and İlki, 2016;Gholoobi et al, 2014). The development of molecular diagnostic techniques has significantly increased sensitivity and reduced diagnosis time (Jung et al, 2016;Lin et al, 2015). PCR-based assays have been used to detect mycobacterial DNA with high sensitivity and specificity (Mackay, 2004;Kwon and Koh, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although semi-automated culture systems have reduced the time required for the tests, traditional tests for identification between MTB and NTM species still suffer from disadvantages (Kazumi and Mitarai, 2012;Şamlı and İlki, 2016;Gholoobi et al, 2014). The development of molecular diagnostic techniques has significantly increased sensitivity and reduced diagnosis time (Jung et al, 2016;Lin et al, 2015). PCR-based assays have been used to detect mycobacterial DNA with high sensitivity and specificity (Mackay, 2004;Kwon and Koh, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our mPCR data based on a large number of MGIT cultures of Mycobacterium species showed that this assay targeting the oxyR-ahpC intergenic region and the variable region of rpoB gene [18] is a rapid, cost-effective and efficient way to differentiate MTB from NTM, and is also capable of identifying mixed MTB + NTM cultures. Other investigators have used more expensive real-time PCR formats with/without expensive probe primers [21, 22]. Although matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has also been used for identification and differentiation of various mycobacteria, the method requires growth on time-consuming solid media for more accurate identification [23, 24].…”
Section: Discussionmentioning
confidence: 99%